Modulating effects of immediate neuroprognosis on early coronary angiography and targeted temperature management following out-of-hospital cardiac arrest: A retrospective cohort study. (October 2019) - Wang, Chih-Hung; Tsai, Min-Shan; Chang, Wei-Tien; Yu, Ping-Hsun; Wu, Yen-Wen; Huang, Chien-Hua; Chen, Wen-Jone
Abstract: Aim: The simplified cardiac arrest hospital prognosis (sCAHP) score is a validated tool for predicting neurological outcomes after out-of-hospital cardiac arrest (OHCA). We used the sCAHP score to evaluate whether the effects of early coronary angiography (CAG) and targeted temperature management (TTM) for OHCA were modulated by immediate neuroprognosis. Methods: This was a single-centre retrospective observational study. Consecutive OHCA patients were screened between 2011 and 2017. Multivariate logistic regression analysis and generalised additive models (GAMs) were used to examine the associations between independent variables and outcomes. Early CAG was defined as CAG performed within 24 h after return of spontaneous circulation (ROSC). Results: A total of 412 patients were included in the study, and 94 (22.8%) patients had neurologically intact survival. The GAM plot identified a sCAHP score of 185 as the cut-off point to differentiate high-risk (sCAHP score ≧185) from low-risk (sCAHP score <185) patients. Regression models indicated that early CAG was significantly associated with favourable neurological [odds ratio (OR) 4.43, 95% confidence interval (CI) 2.28–8.60, p < 0.001] and survival outcomes (OR 3.47, 95% CI 1.93–6.25, p < 0.001), independent of the sCAHP score. Although TTM was associated with favourable neurological outcome only in low-risk patients (OR 2.13, 95% CI 1.10–4.13, p = 0.02), TTM was associated with improved survival for all patients (OR 2.66, 95% CI 1.54–4.59, p < 0.001), independent of the sCAHP score. Conclusions: Early CAG and TTM should be considered for all OHCA patients as suggested by guidelines, irrespective of the immediately predicted neuroprognosis after ROSC.